2001
DOI: 10.1128/mcb.21.15.5214-5222.2001
|View full text |Cite
|
Sign up to set email alerts
|

Chk2 Activation Dependence on Nbs1 after DNA Damage

Abstract: The checkpoint kinase Chk2 has a key role in delaying cell cycle progression in response to DNA damage. Upon activation by low-dose ionizing radiation (IR), which occurs in an ataxia telangiectasia mutated (ATM)-dependent manner, Chk2 can phosphorylate the mitosis-inducing phosphatase Cdc25C on an inhibitory site, blocking entry into mitosis, and p53 on a regulatory site, causing G 1 arrest. Here we show that the ATMdependent activation of Chk2 by ␥-radiation requires Nbs1, the gene product involved in the Nij… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
151
4
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(163 citation statements)
references
References 54 publications
7
151
4
1
Order By: Relevance
“…Several studies showed that the expression of S343A mutant Nbs1 in NBS cells resulted in partial defects in IR-induced S-phase checkpoint activation, radiosensitivity and partial defects in ATM-dependent phosphorylation events including Chk2, SMC1 and FANCD2 (Lim et al, 2000;Buscemi et al, 2001;Nakanishi et al, 2002;Yazdi et al, 2002). Our studies also showed that the MRN complex containing mutant Nbs1 (S343A) failed to stimulate the phosphorylation of Chk2 by ATM although p53 phosphorylation was normal in vitro.…”
Section: Phosphorylation Of Nbs1supporting
confidence: 51%
See 1 more Smart Citation
“…Several studies showed that the expression of S343A mutant Nbs1 in NBS cells resulted in partial defects in IR-induced S-phase checkpoint activation, radiosensitivity and partial defects in ATM-dependent phosphorylation events including Chk2, SMC1 and FANCD2 (Lim et al, 2000;Buscemi et al, 2001;Nakanishi et al, 2002;Yazdi et al, 2002). Our studies also showed that the MRN complex containing mutant Nbs1 (S343A) failed to stimulate the phosphorylation of Chk2 by ATM although p53 phosphorylation was normal in vitro.…”
Section: Phosphorylation Of Nbs1supporting
confidence: 51%
“…The Mre11/Rad50/Nbs1 (MRN) complex has been shown by several groups to be required for the ATM signaling pathway (Lim et al, 2000;Buscemi et al, 2001;Girard et al, 2002;Nakanishi et al, 2002;Yazdi et al, 2002;Uziel et al, 2003). Most of these studies were performed using cells derived from patients with Nijmegen Breakage Syndrome (NBS) or Ataxia-TelangiectasiaLike-Disorder (ATLD), which are caused by hypomorphic alleles of the Nbs1 or Mre11 genes, respectively (Carney et al, 1998;Varon et al, 1998;Stewart et al, 1999).…”
Section: The Role Of the Mrn Complex In Atm Activationmentioning
confidence: 99%
“…This inadequacy is also observed in AT hybrid cells (AT cells6normal cells) (Komatsu et al, 1989). In addition to the defect in intra-S phase checkpoint control, disruption to G2 and G1 checkpoints after irradiation is also observed in NBS cells (Shiloh, 1997;Ito et al, 1999;Buscemi et al, 2001;Girard et al, 2002).…”
Section: Cellular Features Of Nbsmentioning
confidence: 88%
“…In the present study, suppression of Mre11 had direct effects on temozolomide-induced G 2 arrest. The role of the MRN complex in the G 2 -M checkpoint has been controversial, and whereas it has been shown that NBS cells have a defective G 2 -M transition immediately after a low dose of ionizing radiation (47,48), other reports have suggested that the early G 2 -M checkpoint is independent of NBS1 (49, 50). Whereas Mre11 suppression did not seem to alter the ability of cells to undergo G 2 arrest in the present study, it significantly reduced the ability of the cells to maintain this arrest.…”
Section: Discussionmentioning
confidence: 99%